The Influence of Career Agility, Psychological Capital, and Career Adaptability on Teachers’ Career Satisfaction in the Era of Digital Transformation - Atin Supartini; Maman Suratman (Journal Research of Social Science, Economics, and Management, 2026)
Digital transformation has reshaped teachers’ work demands, requiring both career flexibility and psychological readiness. These changes may influence teachers’ career satisfaction, which reflects individuals’ subjective evaluations of their career development and achievements. This study aims to examine the effects of career agility, psychological capital, and career adaptability on teachers’ career satisfaction in the era of digital transformation. This study employed a quantitative approach with an explanatory research design. The research population consisted of teachers at the Yayasan Pembina Pendidikan Teknologi (YPPT) Garut, with total sampling applied. Data were collected through a questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that career agility and psychological capital have positive and significant effects on teachers’ career satisfaction. In contrast, career adaptability shows a negative and non-significant partial effect on career satisfaction. However, when examined simultaneously, career agility, psychological capital, and career adaptability significantly influence teachers’ career satisfaction in the context of digital transformation. These results suggest that teachers’ career satisfaction is more strongly shaped by career agility and psychological capital than by career adaptability.